The effects of leucine-enriched branched-chain amino acid supplementation on recovery after high-intensity resistance exercise - Osmond, A. D.; Directo, D. J.; Elam, M. L.; Juache, G.; Kreipke, V. C.; Saralegui, D. E.; Wildman, R.; Wong, M.; Jo, E. (International Journal of Sports Physiology and Performance, 2019)
Context: Of the 3 branched-chain amino acids (BCAA), leucine has arguably received the most attribution for the role of BCAA supplementation in alleviating symptoms of exercise-induced muscle damage and facilitation of acute performance recovery. Purpose: To examine whether enrichment of a standard BCAA supplement with additional leucine or a standalone leucine (LEU) supplement differentially affects exercise-induced muscle damage and performance recovery compared with a standard BCAA supplement. Methods: A total of 22 recreationally active male and female subjects were recruited and assigned to consume a BCAA, leucine-enriched BCAA (LBCAA), or LEU supplement for 11 d. On the eighth day, subjects performed eccentric-based resistance exercise (ECRE). Lower-body mean average and peak power, plasma creatine kinase, soreness, and pain threshold were measured before and 24, 48, and 72 h after ECRE. Results: LEU showed decreased mean average power (P = .02) and mean peak power (P = .01) from baseline to 48 h post-ECRE, whereas LBCAA and BCAA only trended toward a reduction at 24 hours post-ECRE. At 48 h post-ECRE, BCAA showed greater recovery of mean peak power than LEU (P = .04). At 24 h post-ECRE, LEU demonstrated a greater increase in plasma creatine kinase from baseline than BCAA (P = .04). Area under the curve for creatine kinase was greater in LEU than BCAA (P = .02), whereas BCAA and LBCAA did not differ. Only LEU demonstrated increased soreness during rest and under muscular tension at 24 and 48 h post-ECRE (P < .05). Conclusions: LBCAA failed to afford any advantages over a standard BCAA supplement for postexercise muscle recovery, whereas a LEU supplement was comparatively ineffective.